Association between Serum Follistatin-Like Protein 1 Levels and Disease Activity in Behçet's Disease - Demir, Mesut; Batmaz, Ibrahim; Sariyildiz, Mustafa Akif; Ekinci, Aysun; Akar, Zeynel Abidin; Batmaz, Oznur; Karakoc, Mehmet (Georg Thieme Verlag Kg, 2024)
Introduction This study sought to determine the serum levels of follistatin-like protein 1 (FSTL-1), a glycoprotein of mesenchymal origin shown to be involved in the pathogenesis of many inflammatory diseases, for example Behcet's disease (BD), and to investigate its association with disease activity.Material and Methods The study included 45 patients followed for newly diagnosed Behcet's disease who met the 1990 International Study Group criteria for BD and a control group of 36 healthy volunteers who were age- and gender-matched. Peripheral blood samples were collected from the patients and control groups. Serum FSTL-1 levels were measured using an enzyme-linked immunosorbent assay. The disease activity was assessed using the Behcet's Disease Current Activity Form (BDCAF).Results A comparison of serum FSTL-1 levels in the patient and control groups found significantly higher levels of FSTL-1 in the patient group. Serum FSTL-1 levels were significantly higher in female patients compared with male patients. Female patients exhibited significantly higher BDCAF scores compared with male patients (p=0.008). Erythrocyte sedimentation rate and serum FSTL-1 levels were positively correlated.Conclusion Serum FSTL-1 levels may play a role in the aetiopathogenesis of BD and can also be a useful biomarker for determining disease activity.
Zusammenhang zwischen Follistatin-ähnlichen Protein-1-Stufen im Serum und der Krankheitsaktivität bei Morbus Behçet
Keywords: Follistatin-Like Protein 1; Behcet-Krankheit; Krankheitsaktivitat; Sedimentationsrate der Erythrozyten; disease activity; erythrocyte sedimentation rate; follistatin-like protein 1; Behcet's disease